Markets, enterprises, businessmen (1993)
The 1990-2000 decade is distinguished by the integration of all human being aspects. The having, the doing, the being are integrated and the physical, emotional and intellectual centers are harmonized. This artiele shows how not only the newest paradigm theories but also most unexpected changes in the young consumers choises and preferences are integrated in the same subject "Holistic Learning" and establishes what are the investments preferences of the richest world corporations because of those changes. The article is a clear and concrete simple of how the author, in his management seminaires, obtains an integration between the technical development, the increase of enterprises capacity and the human development of the executives.